Tectono-stratigraphic correlations between Northern Evvoia, Skopelos and Alonnisos, and the postulated collision of the Pelagonian carbonate platform with the Paikon forearc basin (Pelagonian–Vardar zones, Internal Hellenides, Greece). Issue 1 (24th April 2020) - Scherreiks, Rudolph; Boudagher-Fadel, Marcelle
Abstract : page_1 other The Pelagonian stratigraphy of the Internal Hellenides consists of a Permo-Triassic basement and an Upper Triassic and Jurassic carbonate platform formation that has been overthrust by the Eohellenic ophiolite sheet during the Early Cretaceous. Intensive erosion, during the Cretaceous, removed most of the ophiolite and parts of the Jurassic formation. It is hypothesised that uplift and erosion of eastern Pelagonia was triggered by the break-off of the subducted oceanic leading edge of the Pelagonian plate. An investigation of the rocks that succeed the erosional unconformity shows that they constitute a shear-zone that is tectonically overlain by Cretaceous platform carbonates. Geochemical analyses of the shear-zone rocks substantiate that they are of mid-oceanic ridge and island arc provenience. Eastern Pelagonia collided with a Cretaceous carbonate platform, probably the Paikon forearc basin, as the Almopias ocean crust subducted beneath that page_2 other island–arc complex. The Cretaceous platform, together with a substrate of sheared-off ocean floor mélange, overthrust eastern Pelagonia as subduction continued, and the substrate was dynamically metamorphosed into cataclastic rocks, mylonite, phyllonite and interpreted pseudotachylite. This complex of Cretaceous platform rocks and a brittle-ductile shear-zone-substrate constitute the here named Paikon–Palouki nappe, which was emplaced during Early Palaeocene. The Paikon–Palouki nappe did not reach Evvoia. Seismic tomographic models of the Aegean region apparently depict images of two broken-off ocean-plate-slabs, interpreted as Almopias-lithosphere-slabs. It is concluded that the western Almopias slab began to sink during the Early Cretaceous, while the eastern Almopias slab broke off and sank after the Paikon–Palouki nappe was emplaced in the Early Palaeocene.